O TAKE OFF de um professor estagiário e dos alunos rumo a uma Educação Física na e para a diversidade de alunos - André Filipe Ferreira Martins (2023)
This report depicts the journey of a pre-service teacher (the author) during the school placement. It represents the experience, before and after, of a teacher in search of academic knowledge for personal and professional development. This is the culmination of an academic process, but the starting point for a "take off" towards emancipation as a future teacher. Supervised teaching practice brings us into initial contact with the profession, fostering experiences, challenges, reflections, and learning. The school placement took place in a school in the metropolitan area of Porto. Throughout this report, the major planning decisions are presented, which always had the aim of promoting quality teaching and fostering students' motivation for the subject. The process of reflection on the practice was something that always accompanied me, proving to be remarkable for my training as pre-service teacher. The use of assessment for learning resulted in excellent discoveries because it puts the students at the centre of the educational process, leading them to build their own learning. This report also includes a research study with the aim of considering the diversity of students in a physical fitness for health programme using reciprocal teaching. The results show that most students adhered positively to the training programme and improved their physical fitness levels. Reciprocal teaching has proved to be a strategy that fosters students' cooperation and autonomy, as well as their acquisition of knowledge throughout their training programmes. The students revealed high levels of satisfaction and motivation to practice. The professional internship takes on an important phase in the development of the pre-service teacher. This represented a progressive liberation in search of knowledge to become a better teacher. KEYWORDS: